Growth intention and growth in small accounting firms - Lars Kolvereid; Bjørn Willy Åmo (Administrative Sciences, 2019)
Previous research has found that owner/manager growth intention is related to subsequent firm growth, but growth intention alone only explains about 4-5% of the variance in actual firm growth. The purpose of this study is to investigate factors in addition to growth intention that may help us to explain a higher proportion of the variance in firm growth. We selected three factors for our study: Entrepreneurial orientation, versatile human resources and labor productivity. We tested the hypotheses in a sample of small Norwegian accounting firms. The findings indicate that, after controlling for growth intention, versatile human resources and labor, productivity contributed to the explanation of the variance in sales and employment growth, while entrepreneurial orientation has no such additional effect.
Keywords: 350; growth intention; growth in sales; growth in employment; accounting firms